Особенности электрохимического осаждения тугоплавких сплавов на алмазах - Дуда, Т.М.; Кухаренко, С.А.; Шатохин, В.В.; Довгань, А.Г.; Хрипкова, Л.Д. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The analysis of theoretical foundations of electrochemical separation of refractory elements
(tungsten and molybdenum) from aqueous solutions of electrolytes and practical production of refractory
alloys (nickel-tungsten and nickel-molybdenum) for diamond grit’s metal coatings is
shown. The influence of current load on the metallization degree and alloy output current is established.
The structure of the surface coatings, their composition and effect of composition on the
dynamic strength of coated diamond powders are defined. The areas for further work on granulation
of high-strength metal-coated diamond grits and the creation of heterogeneous wear-resistant
metal-diamond structures are identified.